PENERAPAN SUMBER IDE LAMBU AYU DALAM PEMBUATAN BUSANA PESTA GALA - Ms Jumariah; Della Novita Sari (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2022)
The objectives of this study are 1) Pouring out the source of lambu ayu's idea in making gala party fashion, 2) Applying sequin decoration in the manufacture of gala party fashion using songket tawur cloth combined with bludru fabric. This research uses descriptive research to obtain an overview of the making of gala party clothes with the source of the lambu ayu story idea. The research design uses a qualitative approach by describing and interpreting the panellist test data through the FGD of the research results, the focus of attention on the flower petals on the neck of the clothes, and the combination of songket and velvet material colours. Data collection using the method: 1) Descriptive focus discussion / FGD, 2) Data analysis documentation (descriptive data analysis). Based on the results of research on the application of the source of the lambu ayu idea in making gala party clothes, it can be concluded: The lime petal-shaped attention centre is declared very appropriate, and the combination of songket and bludru fabric colours is declared harmonious while the application of the source of the idea shows that it is very suitable.